NURSING CARE FOR MR. A WITH ENDOCRINE SYSTEM DISORDER: TYPE II DIABETES MELLITUS IN THE 2ND FLOOR WARD A OF PUTRI BIDADARI GENERAL HOSPITAL, ACEH - Sarah Musfira; Vira Adelia; Liwaul Hamdi; M. Aidil Zulkiram; Muhammad Hayzir Yuhdi; Hasanul Maula (Jurnal Penelitian Progresif, 2026)
Type II Diabetes Mellitus (DM) is a chronic metabolic disease characterized by hyperglycemia caused by impaired insulin secretion and insulin resistance. This disease has become a global health problem with a prevalence that continues to increase each year and may lead to various complications, such as neuropathy, nephropathy, retinopathy, and cardiovascular disorders. Therefore, comprehensive management through appropriate nursing care is essential. This case study aimed to describe the implementation of nursing care for a patient with Type II Diabetes Mellitus in the 2nd Floor Room A of Putri Bidadari General Hospital, Aceh. The method used was a case study approach applying the nursing process, including assessment, nursing diagnosis, intervention, implementation, and evaluation. The assessment results in Mr. A revealed complaints of weakness, frequent urination, excessive thirst, and elevated blood glucose levels. The nursing diagnoses identified included unstable blood glucose levels, nutritional deficits, risk of impaired skin integrity, and activity intolerance. Nursing interventions included monitoring blood glucose levels, providing diabetes diet education, administering therapy according to the medical program, monitoring vital signs, and assisting with daily activities. Nursing care was implemented continuously and evaluated based on the patient’s progress. The evaluation results showed improvement in the patient’s general condition, reduced complaints, and increased knowledge regarding the management of Type II Diabetes Mellitus. Comprehensive and continuous nursing care plays an important role in controlling the disease, preventing complications, and improving the quality of life of patients with Type II Diabetes Mellitus.